CONVERSION & OPTIMIZATION OF PILOT PLANT DATABASE - Jofri, Akmaruddi (Universiti Teknologi Petronas, 2005)
A database system by ICONICS was used for Pilot Plant in Plant Process Control Laboratory of Universiti Teknologi Petronas. The Pilot Plant employs a Distributed Control System and simulates a basic process control system. Users of the database find it difficult to use the data to be utilized in other software such as Matlab because of its improperarrangement of data. Thus, main concern in this project is to convert the database file obtained from the UTP Pilot Plant to another file with better arrangement of data. An offline converter application has been successfully developed by using Visual Basic 6, which can convert the database to another smaller size file with the desired arrangement of data. The online converter was developed but could not be completed on time. Issues and problems regarding both offline and online converter application will be discussed thoroughly through out this report.